2016
DOI: 10.1186/s12886-016-0232-2
|View full text |Cite
|
Sign up to set email alerts
|

Biometry and visual function of a healthy cohort in Leipzig, Germany

Abstract: BackgroundCross-sectional survey of ocular biometry and visual function in healthy eyes across the life span of a German population aged 20 to 69 years (n = 218). Subject number in percent per age category reflected the percentage within the respective age band of the population of Leipzig, Germany.MethodsMeasurements obtained: subjective and objective refraction, best-corrected visual acuity, accommodation, contrast sensitivity, topography and pachymetry with Scheimpflug camera, axial length with non-contact … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

15
35
3
5

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(59 citation statements)
references
References 80 publications
15
35
3
5
Order By: Relevance
“…A deeper anterior chamber in myopic subjects has been reported to be present in middle age and elderly individuals in many studies 13,29,32,36,37 . However, the relationship between the central corneal thickness and myopia is contradictory.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…A deeper anterior chamber in myopic subjects has been reported to be present in middle age and elderly individuals in many studies 13,29,32,36,37 . However, the relationship between the central corneal thickness and myopia is contradictory.…”
Section: Discussionmentioning
confidence: 94%
“…However, the relationship between the central corneal thickness and myopia is contradictory. Some studies reported that the central corneal thickness was not significantly correlated with the myopia 33,36,38,39 , other studies reported that there was a positive correlation between the central corneal thickness and the myopia 19,40 , and other studies reported a negative correlation between them 20,22,24 . Although, studies that reported a significant correlation between the central corneal thickness and refractive error, the correlation coefficients were relatively weak, and the significant correlation was seen in only the simple linear regression analysis.…”
Section: Discussionmentioning
confidence: 99%
“…A good agreement with axial length changes is seen (Figure 2a), with r 2 = 0.486 (P < 0.001) by using body length and education levels for the period 1910-1990, averaged across all of the countries involved, into the model. Since body length and education both increased with year of birth, special care had to be taken to handle the strong non-causal correlation between them (Pearson r = 0.845) when considering the model with either body length or 6 Hong Kong 182 40-75 A-scan Yes (↓) Ooi 14 New Zealand 96 19-61 A-scan No Wong 7 Singapore 1004 40-81 A-scan Yes (↓) Wickremasinghe 15 Mongolia 1617 40-70+ A-scan No Gudmundsdottir 8 Iceland 757 50-96 A-scan Yes (↓) Shufelt 9 USA 5588 40-80+ A-scan Yes (↓) Warrier 17 Myanmar 1498 40-70+ A-scan No He 18 China 1196 50-93 A-scan No Lee 10 USA 1967 58-100 Optical Yes (↓) Foster 11 UK 2519 48-48 Optical Yes (↓) Fotedar 12 Australia 1321 59-85+ Optical Yes (↓) Nangia 19,34 India 3397 30-100 A-scan Yes (↑) Hashemi 13 Iran 4869 40-64 Optical Yes (↓) Zocher 20 Germany 218 21-69 Optical No He 21 China 6099 Optical No Figure 1. Overview of articles reporting axial length as a function of age based on the cross-section of a population.…”
Section: Cohort Artefactmentioning
confidence: 99%
“…Overview of articles reporting axial length as a function of age based on the cross-section of a population. [4][5][6][7][8][9][10][11][12][13][14][15][17][18][19][20][21] education level. For this reason, as well as the widely varying ranges in year of birth between studies, both parameters were averaged into 5 cm bins for body length ( Figure 2b) and 2-year bins for education level.…”
Section: Cohort Artefactmentioning
confidence: 99%
“…Continuous flattening of anterior chamber (AC) and ocular crystalline lens Correspondence to: Muhammad Arslan Ashraf BS Vision Sciences, Email: rajkumararslan@yahoo.com thickening is the best example of such structural changes with increasing age. 1 In current century, advances in cataract surgery techniques have made ocular biometry more and more important. Instead of advancement in cataract surgery techniques, the accuracy is still dependent on precise biometry technique.…”
Section: Introductionmentioning
confidence: 99%